A fast modeling approach for numerical analysis of unreinforced and FRCM reinforced masonry walls under out-of-plane loading - Scacco, Jacopo (2020)
A new discretized homogenization approach is proposed in this study in order to predict the behavior of unre-inforced and FRCM reinforced masonry structures. The proposed approach allows overcoming the common disadvantages of the existing homogenization approaches: (a) being difficult to implement and (b) not allowing to couple the in-plane and out-of-plane actions. Reference experimental results and detailed numerical modeling are used for validation of the proposed modeling strategy. In the proposed model, the elastic cells are linked by homogenized interfaces. The mechanical properties coming from the homogenization procedures are lumped at the interfaces by means of the generic Concrete Damage Plasticity model, allowing easy implementation and avoiding computational issues peculiar to other approaches available in the literature. The new approach shows accurate results in predicting the global behavior and the damage pattern for both unreinforced and FRCM strengthened masonry walls. The results are promising also with a view to be applied for more complex reinforced applications as double curvature masonry structures.